Peridynamics for bending of beams and plates with transverse shear deformation. (September 2015) - Diyaroglu, C.; Oterkus, E.; Oterkus, S.; Madenci, E.
Abstract: Progressive failure analysis of structures is still a major challenge. There exist various predictive techniques to tackle this challenge by using both classical (local) and nonlocal theories. Peridynamic (PD) theory (nonlocal) is very suitable for this challenge, but computationally costly with respect to the finite element method. When analyzing complex structures, it is necessary to utilize structural idealizations to make the computations feasible. Therefore, this study presents the PD equations of motions for structural idealizations as beams and plates while accounting for transverse shear deformation. Also, their PD dispersion relations are presented and compared with those of classical theory.